Pasteurelose em juvenis de cobias (Rachycentron canadum) criados em tanques-redes no litoral norte do estado de São Paulo - Brasil - Shimada, Marina Tie [UNESP] (2015)
The cobia (Rachycentron canadum) shows great potential for marine fish farming in Brazil. As in any production activity, the intensification submit the fish to the high stocking density and alteration of the natural habit of the species. These factors cause stress, reduce the efficiency of the immune system and predispose fish to diseases. This study aimed to establish the diagnosis of high mortality in juvenile cobias raised in cages on the northern coast of São Paulo. The mariculture began in November 2010, the first cycle of fattening cobias with 24,000 fingerlings and in September 2011 remained about 500. The diagnostic plan began in March 2011, with necropsy and collection integument, gills, heart, liver, spleen, kidney and pyloric caeca for histopathological analysis (n = 8). After analysis, the fish mortality was related to pasteurellosis, a septicemic bacterial disease caused by Photobacterium damselae subsp piscicida. In May, July and September were collected liver, spleen, heart and kidney for bacteriological examination (n = 15) as well as same samples collected in March to histopathology (n = 38). Bacterial isolates were subjected to molecular analysis to confirm disease. No Mycobacterium sp. In macroscopic, whitish nodules with about 0.5 mm were observed in the liver and kidney. Neobenedenia melleni and Tuxophorus caligodes were the parasites identified mainly present in the head. In microscopy, we evaluated 46 fish of which 94% had liver granulomas containing necrotic center and agglomeration of bacteria delimited by epithelioid cells and extensive fibroplasia. The Ziehl Neelsen was negative for alcohol acid resistant bacteria. The liver of 92% of fish had severe and extensive vacuolization in the cytoplasm of hepatocytes. The Sudan Black stain identified the presence of lipids confirming steatosis. The regression of steatosis was noted from July, when the trash fish was included in the diet. The diagnosis of high ...